Symptomatic therapy for chronic joint diseases - Galina Rashidovna Imametdinova; N V Chichasova; E L Nasonov; E V Igolkina (Современная ревматология, 2010)
The paper depicts the aspects of symptomatic therapy for chronic inflammatory diseases of joints and the mechanisms of action of nonsteroidal anti-inflammatory drugs. It gives the data available in the literature on the efficacy of Voltaren (diclofenac sodium) and pharmacodynamic differences of original Voltaren and its generics.